Genomic diversity and the domestication history of cotton ( Gossypium hirsutum ) - Weixuan Ning; Mark A. Arick; Joshua A. Udall; Chuan-Yu Hsu; Luis Abdala-Roberts; Uriel Solís-Rodríguez; Yeyson Briones-May; Zenaida V. Magbanua; Olga Pechanova; Carlos Bustos-Segura; Mary V. Clancy; Sandra Díaz-Cruz; et al. (Proceedings of the National Academy of Sciences, 2026)
Gossypium hirsutum is the leading fiber crop globally, but its origin as a domesticated plant and patterns of diversity in the wild remain to be elucidated. Here, we use extensive sampling of wild populations and comparative genome sequence data to illuminate the scope and patterning of wild cotton diversity across its native range. Analyses confirm the hypothesis that the Yucatán Peninsula (México) is the center of domestication, from which the original perennial forms and later modern annualized cultivars were derived. Population structure and phylogenomic analyses indicate that northwestern Yucatán harbors greater genetic diversity relative to smaller, geographically dispersed populations in northeastern Yucatán and the Caribbean basin. Genetic load and transposable element burden also are the lowest in northwestern Yucatán relative to other regions, consistent with its greater diversity and reflecting the effects of historical genetic bottlenecks in other populations. Populations from Florida and elsewhere in the Caribbean basin maintain unique pockets of diversity. Analyses of selection suggest that cotton domestication entailed long-term accumulation of mutations with relatively minor phenotypic effects, as opposed to a more punctuated process involving major domestication genes. Our study quantifies the scope and scale of genomic diversity in wild cotton, the origin of the cultivated gene pool, and the likely ecological and anthropogenic processes that shaped extant diversity and modern geographic patterning.